Hsa_circ_0028502 and hsa_circ_0076251 are potential novel biomarkers for hepatocellular carcinoma. (8th October 2019) - Jiang, Zhenluo; Shen, Lili; Wang, Shuwei; Wu, Shengdong; Hu, Yaoren; Guo, Junming; Fu, Liyun
Abstract: Circular RNAs (circRNAs) have been increasingly revealed to be desirable biomarkers for some tumors, including hepatocellular carcinoma (HCC). Combined with our previous microarray screening results, we aimed to determine the hsa_circ_0028502 and hsa_circ_0076251 expression features in HCC, analyze the relationship between their expression level and clinical and pathological characteristics, and investigate their diagnostic and prognostic values. Our data demonstrated that the hsa_circ_0028502 and hsa_circ_0076251 levels were considerably lower in HCC tissues than in adjacent paracancerous tissues ( P  < .001). Further study revealed that hsa_circ_0028502 expression levels were related to tumor node metastasis (TNM) stage ( P  = .015) and that hsa_circ_0076251 expression levels were related to Barcelona Clinic Liver Cancer (BCLC) stage ( P  = .038), comorbidity with type 2 diabetes mellitus ( P  = .023) and the presence of serum HbsAg ( P  = .044). Furthermore, the degree of expression of both hsa_circ_0028502 and hsa_circ_0076251 increased from HCC to liver cirrhosis (LC) to chronic hepatitis (CH). The receiver operating characteristic (ROC) curve demonstrated that hsa_circ_0028502 and hsa_circ_0076251 could serve as fairly accurate markers to distinguish HCC tissues from CH tissues and LC tissues, as well as distinguishing LC tissues from CH tissues. Cox regression analysis showed that low expression of has_circ_0076251 was associated with unfavorable survival rates in HCC (HR = 0.46; 95% CI = 0.22‐0.98; P  < .05). These findings implied that hsa_circ_0028502 and hsa_circ_0076251 were potentially valuable biomarkers for HCC diagnosis, whereas hsa_circ_0076251 could be used as a prognostic indicator for HCC. Abstract : hsa_circ_0028502 and hsa_circ_0076251 are potentially valuable biomarkers for HCC diagnosis, and meanwhile, hsa_circ_0076251 could serve as a prognostic indicator for HCC.